Determination of ionospheric parameters in real time using SuperDARN HF Radars. Issue 7 (17th July 2014) - Bland, Emma C.; McDonald, Andrew J.; de Larquier, Sebastien; Devlin, John C.
Abstract A technique for determining key ionospheric parameters from high‐frequency (HF) over‐the‐horizon radar ground scatter data is investigated using two Southern Hemisphere SuperDARN radars and also a Northern Hemisphere SuperDARN radar with reliable elevation angle‐of‐arrival capability. Ground scatter data are analyzed over a range of frequencies from 8 to 18 MHz to determine the maximum usable frequency and the vertical critical frequency over a wide geographical area within the radar field of view. The technique is shown to be well suited to middle to high latitudes where backscatter echoes from the ground dominate over those from ionospheric scattering targets. However, the technique is shown to break down during the winter months and away from solar maximum. It is shown that the use of reliable elevation angles can greatly enhance such methods allowing discrimination between ground scatter propagating via the E and F regions. It is also shown that contamination from very low velocity ionospheric scatter and ground scatter originating from the back lobe of the radar can be effectively filtered out, with the use of reliable elevation angles. This greatly improves the reliability of the ionospheric data products and allows for a high degree of automation of the process.